Constitutionality of Implementing Asymmetric Lockdown (Regional Quarantine) When Covid-19 Increases to Accelerate Health Emergency Management - Fauzia, Ana; Al Khori, Bayu Yusya Uwaiz; Rahayu, Puji (Law Research Review Quarterly, 2022)
The constitution is the basis for all the space for a country to move, whether the country is in normal or abnormal conditions. It based on the constitution as the basic norm that is the highest guideline for a country. In the case of an abnormal state, Posner explains that there is flexibility needed to deal with abnormal conditions in the constitution. Indonesia declared the country's status in a health emergency based on Presidential Decree Number 11 of 2020 on the Determination of a Corona Virus Disease Public Health Emergency and Government Regulation In Lieu Of Law Number 1 of 2020 on State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic and/or In Facing Threats That Endanger the National Economy and/or Financial System Stability that cause the economy to decline and conflict in society. The government is faced with policy choices in dealing with this Covid. In Indonesia, the real meaning of lockdown is regional quarantine. The area quarantine itself is regulated in Law Number 6 of 2018 on Health Quarantine (Health Quarantine Law). Although Indonesia has been able to adapt to Covid-19, it is possible that in the future there will be a genetic mutation of this virus, causing an increase in the spread of Covid-19. Therefore, before there is a spike in Covid-19 in the future, it must be clear in the division of authority both in the central government and regional governments regarding the lockdown (regional quarantine).